Relations between Turkey and Syria in the 1980's and 1990's: Political Islam, Muslim Brotherhood and Intelligence Wars - (:unkn) unknown (ULUSLARARASI ILISKILER KONSEYI DERNEGI, 2019)
The aim of this study is to examine how continuities and discontinuities over a period of nearly half a century have shaped the AKP government's relationship with the Syrian Muslim Brotherhood and the Assad regime. From the start of the 1980s until the 2011 Arab Uprisings, relations between Turkey, Turkish Islamists, Syria, and the Syrian Muslim Brotherhood remained highly complex. Based on the information available from open sources and newspaper archives, this study terms the conflict between the Turkish and Syrian intelligence services that broke out in the 1980s as an intelligence war. Both countries viewed the PKK and the Muslim Brotherhood - domestic enemies which they were trying to stamp out - as useful actors to be played off against the other party. While the Syrian/PKK part of the equation was frequently alluded to by the Turkish media and Turkish academia, Turkey's relations with the Muslim Brotherhood were gradually forgotten. Though open support for the Brotherhood was never an element in Ankara's official foreign policy, Turkey's intelligence and security forces did establish ties to the Brotherhood in order to strengthen Turkey's hand against Syria and made use of the organization insofar as it was in their interest to do so.
Keywords: Turkey's Foreign Policy; Syria; Muslim Brotherhood; Political Islam; Cold War; Anti-communism